An assessment of the implementation of new science and technology curriculum - Goemleksiz, Mehmet Nuri; Bulut, Ilhami (Hacettepe Univ, 2007)
The aim of this study is to determine the effectiveness of the new primary school Science and Technology curriculum in practice based on teachers' opinions. For that aim, a 32 item Likert style Science and Technology Curriculum Scale was developed. The population includes 383 classroom teachers working at 64 pilot schools where the new Science and Technology Curriculum was trialled in Istanbul, Ankara, Izmir, Kocaeli, Van, Hatay, Samsun and Bolu cities. The data were analyzed by using independent samples t test, one way ANOVA, Kruskall Wallis H, Mann Whitney U and LSD tests. According to the results obtained from the study, it was determined that the learning attainments, content, teaching-learning activities and evaluation were effective at much level. While statistically significant difference was found among the teachers' views in terms of city variable, no significant difference was found in terms of student number variable.
Keywords: primary school; science and technology curriculum; curriculum development